2020
DOI: 10.1063/5.0009903
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the passive pulsation of a surface-attached air bubble subjected to a nearby oscillating spark-generated bubble

Abstract: The dynamics of a spark-generated bubble (a discharge short circuit) generated in proximity to a stationary air bubble attached to a plate is experimentally investigated by high-speed photography. Numerous interesting and complex interactions occur during the two bubble coupling pulsation owing to the deformation properties or “free surface” characteristics supplied to the plate by the attached air bubble. Complex bubble jetting behaviors, such as bubble splitting, jets away from the plate, variable directiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…The jet direction is calculated to be 26 according to Eq. ( 11), which is consistent with the result based on the measurement of the bubble profile in the experimental image (25 ). Note that we define the jet direction by the Kelvin impulse, characterizing the movement trend of bubbles.…”
Section: Validation Of Numerical Modelsupporting
confidence: 89%
See 1 more Smart Citation
“…The jet direction is calculated to be 26 according to Eq. ( 11), which is consistent with the result based on the measurement of the bubble profile in the experimental image (25 ). Note that we define the jet direction by the Kelvin impulse, characterizing the movement trend of bubbles.…”
Section: Validation Of Numerical Modelsupporting
confidence: 89%
“…One of the most important and interesting features of bubble dynamics near a rigid wall is the creation of high-speed liquid jets. 1,[23][24][25][26][27][28][29][30][31] These jets point toward the wall in the case of small-scale bubbles and interact with the flow field close to the wall. In the late stage of bubble collapse, they may even hit the wall.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have found that near the water–air free interface or bubbles, cavitation bubbles can generate jets away from the interface or bubbles [14] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] . Gonzalez et al [32] fabricated mushroom-shaped microcavities on SiO2/Si substrates, which can effectively capture air underwater.…”
Section: Introductionmentioning
confidence: 99%